PEKERJAAN LUAR USAHATANI (KASUS RUMAH TANGGA PETANI GUREM DI JAWA) - Ken Suratiyah (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2001)
Small farmer's household never deppend on on-farm income, they must to get other income sources by allocating their family labour as must as possible.Although they are small farmers, they still regard their job is being farmer and the other off-farm activities just as part time jobs. Family labour allocation on off-farm activities is about four times then on-farm, the off-farm's share to household income are 60,31%.By off-farm activities household farmer welfare level increase from poverty level to become wealthy level or not be poor level. The fact is show that off-farm activities to become more important for small farmer's household.